Elbow flexion reconstruction with nerve transfer or grafting in patients with brachial plexus injuries: A systematic review and comparison study. Issue 1 (13th February 2019) - Ayhan, Egemen; Soldado, Francisco; Fontecha, César G.; Bertelli, Jayme A.; Leblebicioglu, Gursel
Abstract : Introduction: Posttraumatic brachial plexus (BP) palsy was used to be treated by reconstruction with nerve grafts. For the last two decades, nerve transfers have gained popularity and believed to be more effective than nerve grafting. The aim of this systematic review was to compare elbow flexion restoration with nerve transfers or nerve grafting after traumatic BP injury. Methods: PRISMA‐IPD structure was used for 52 studies included. Patients were allocated as C5‐C6 ( n = 285), C5‐C6‐C7 ( n = 150), and total BP injury ( n = 245) groups. In each group, two treatment modalities were compared, and effects of age and preoperative interval were analyzed. Results: In C5‐C6 injuries, 93.1% of nerve transfer patients achieved elbow flexion force ≥M3, which was significantly better when compared to 69.2% of nerve graft patients ( p < 0.001). For improved outcomes of nerve transfer patients, shorter preoperative interval was a significant factor in all injury patterns ( p < 0.001 for C5‐C6 injuries and total BP injuries, p = 0.018 for C5‐C6‐C7 injuries), and young age was a significant factor in total BP injury pattern ( p = 0.022). Conclusions: Our analyses showed that nerve transfers appear superior to nerve graftings especially in patients with a C5‐C6 injury. Unnecessary delays in surgery must be prevented, and younger patients may have more chance for better recovery. Level of evidence: Level II.